Physical and Oxidative Stabilization of Omega-3 Fatty Acids in Surimi Gels - Tolasa, Sebnem; Lee, Chong M.; Cakli, Sukran (Journal of Food Science, 2010)
The objective of the study was to compare the dispersion and oxidative stability of omega-3 fatty acid oil in high- and low-quality surimi gels during 4-mo refrigerated and frozen storage. Low-quality surimi was prepared by subjecting Alaska pollock surimi to 7 freeze-thaw cycles. Surimi gels were prepared with 4% modified starch, 2% salt, and 0.5% or 1% algal DHA or concentrated fish EPA-DHA oil, and stored at -18 or 3 °C for 4 mo after being vacuumed packed and pasteurized. The effect of surimi gel properties on oil dispersion was examined using light microscopy equipped with image process software. The extent of lipid oxidation was monitored by thiobarbituric acid reactive substances (TBARS), peroxide value (PV), and fatty acid methly esters (DHA and EPA). Very fine and uniform oil dispersion was observed in the high-quality surimi gel with the average droplet size of 12.37 μm2 and dispersion of 1.73 × 10-3 droplets/μm2 compared to 84.32 μm2 and 0.57 × 10-3 droplets/μm2 in the low-quality gel. Throughout the 4 mo storage, TBARS and PV of high-quality surimi gel were significantly (P < 0.05) lower than those of low-quality surimi gel. The decreases in omega-3 fatty acids in the high-quality surimi gels were lower than those in the low-quality surimi gels under both storage conditions. Results confirm that a highly cohesive gel matrix is required to have a fine dispersion and oxidative stability of omega-3 fatty acids in the surimi gel system.Practical Application: Uniform dispersion and oxidative stability of omega-3 fatty acid oil can be achieved in the highly cohesive surimi gel system without use of antioxidants. This suggests that surimi can be used as a protein-based carrier in developing high omega-3 fatty acids-containing seafood products. © 2010 Institute of Food Technologists®.